Detection of high-frequency hearing loss among hospital staffs exposed to occupational noise using extended pure tone audiometry - Umbaik, Norsyamira Aida Mohamad (2019)
Detection of high-frequency hearing loss among hospital staffs exposed to occupational noise using extended high-frequency pure tone audiometry Objectives: To determine the prevalence of extended high-frequency (EHF) hearing loss, the association between noise exposure and EHF hearing loss and its associated factors among hospital staff working in noisy environment. Methods:This was a comparative cross-sectional study involving 140 hospital staffs (70 participants from noise-exposed group and 70 participants from non-noise exposed group). The hearing was tested using conventional and EHF pure tone audiometry (PTA) up to 16 kHz. The prevalence of EHF hearing loss was calculated.The chi-squares tests were performed to determine the association between noise exposure and conventional PTA and EHF PTA hearing loss. The chi-square test was also used to determine the association between duration of noise exposure and EHF hearing loss. Multiple logistic regression analysis was performed to determine the factors associated with EHF hearing loss. The p-value of less than 0.05 was considered as statistically significant. Results:The prevalence of abnormal conventional PTA in noise-exposed hospital staff was 22.9%, while the EHFhearing loss was 81.4%. Meanwhile, among the control group the abnormal conventional PTA was seen in 11 participants (15.7%), with 53 participants (75.7%) have an abnormal EHF PTA. We found that there was no significant association between noise exposure and EHF hearing loss. However, there was a significant association between duration of noise exposure and EHF hearing loss. Age was a significant factor for an exposed participants to have EHF hearing loss, while gender, smoking and noise exposure were not. Conclusion:The present study showsthat EHF PTA gives no additional benefit compared with conventional PTA in detecting noise-induced hearing loss. However, EHF PTA can be used as an adjunct to conventional PTA for early detection of hearing loss among noise-exposed workers.